Upaya Memupuk Jiwa Nasionalisme Anak Didik Rumah Pintar Yayasan Dolok Marsait Membangun di Masa Pandemi - Yuli Harum Mayarli Sidabutar; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2022)
The soul and values ​​of nationalism are very important to apply to students. In an effort to develop a spirit of nationalism in students, Rumah Pintar the Dolok Marsait Foundation, builds during a pandemic, which is one of the activities carried out for the children of the nation's generation, with the hope that it will foster a sense of love for the motherland and instill the values ​​of nationalism and Pancasila. The purpose of carrying out this activity is to instill a spirit of nationalism by introducing national and national anthems to students, sharpening the meaning of Pancasila as the basis of the state so as to foster a sense of love for the motherland and instill nationalism and Pancasila values ​​in students as the next generation of the nation so that created morals and morals in accordance with existing values. The target of this activity is students studying at the Dolok Marsait Foundation's smart house to build in order to create a generation of nations who have character with the spirit of defending the country and love for the motherland. This activity lasts for approximately 3 months which is carried out at each learning meeting. From this activity it can be seen that a sense of togetherness and nationalism grows within the students.